2010
DOI: 10.1007/s10533-010-9520-8
|View full text |Cite|
|
Sign up to set email alerts
|

N2O and CH4 fluxes in undisturbed and burned holm oak, scots pine and pyrenean oak forests in central Spain

Abstract: We investigated N 2 0 and CH 4 fluxes from soils of Quercus ilex, Quercus pyrenaica and Pinus sylvestris stands located in the surrounding área of Madrid (Spain). The fluxes were measured for 18 months from both mature stands and post fire stands using the static chamber technique. Simultaneously with gas fluxes, soil temperature, soil water content, soil C and soil N were measured in the stands. Nitrous oxide fluxes ranged from -11.43 to 8.34 ug N 2 0-N m~2 h" 1 in Q.üex, -1.1 A to 13.52 ug N 2 0-N m -2 h _1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 79 publications
1
9
0
Order By: Relevance
“…They considered aerobic denitrification by heterotrophic nitrifiers as a possible pathway, denitrifying bacteria might use atmospheric N 2 O as an alternative electron acceptor to nitrate when the latter was in short supply. Moreover, Inclán et al (2012) demonstrated that N 2 O sink was possibly attributed to high total dissolved organic carbon content and high SM, combined with low levels of SM and nitrogen. However, N 2 O sinks have often been overlooked and the driving factors for these sinks are poorly understood (Goldberg and Gebauer, 2009;Stewart et al, 2012).…”
Section: N 2 Omentioning
confidence: 98%
See 1 more Smart Citation
“…They considered aerobic denitrification by heterotrophic nitrifiers as a possible pathway, denitrifying bacteria might use atmospheric N 2 O as an alternative electron acceptor to nitrate when the latter was in short supply. Moreover, Inclán et al (2012) demonstrated that N 2 O sink was possibly attributed to high total dissolved organic carbon content and high SM, combined with low levels of SM and nitrogen. However, N 2 O sinks have often been overlooked and the driving factors for these sinks are poorly understood (Goldberg and Gebauer, 2009;Stewart et al, 2012).…”
Section: N 2 Omentioning
confidence: 98%
“…Soil water status thus appear to be important driving factors for N 2 O capture (Goldberg and Gebauer, 2009;Peichl et al, 2010;Gundersen et al, 2012). Forest soils serving as sinks for atmospheric N 2 O have been reported across a broad spectrum of studies (Chapuis-Lardy et al, 2007;Kellman and Kavanaugh, 2008;Peichl et al, 2010;Eickenscheidt and Brumme, 2012;Inclán et al, 2012;Ma et al, 2012;Stewart et al, 2012). Rosenkranz et al (2006) pointed out that the negative N 2 O fluxes were mainly due to very low N availability and high soil C content.…”
Section: N 2 Omentioning
confidence: 99%
“…We assumed that the parameters explaining best the variation of N 2 O fluxes were soil temperature and soil water content. N 2 O production in soils is primarily driven by microbial processes, including nitrification and denitrification, which are related to soil temperature (Inclan et al, 2012). High soil water content can not only stimulate soil microbial activities, but also restrict oxygen diffusion and reduce oxygen concentration in soils, resulting in higher denitrification rates under anaerobic conditions .…”
Section: N 2 O Emissionsmentioning
confidence: 99%
“…The majority of studies have focused on the exchange of the most important greenhouse gas, CO 2 . However, N 2 O and CH 4 are associated with long-wave solar radiation and play important roles in climatic warming (Inclan et al, 2012). For example, CH 4 is approximately 25 times more powerful in warming the atmosphere than CO 2 for the horizon of 100 years (Chen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation